A Comparative Efficacy Study of Robotic Priming of Bilateral Approach in Stroke Rehabilitation - Li, Yi-chun; Lin, Keh-chung; Chen, Chia-ling; Yao, Grace; Chang, Ya-ju; Lee, Ya-yun; Liu, Chien-ting (Frontiers in Neurology, 2021)
Background: Stroke survivors can remain impaired in body functions, activity, and participation. A novel rehabilitation regimen is required to obtain scientific evidence and to help clinicians determine effective interventions for stroke. Mirror therapy (MT) and bilateral upper limb training (BULT) are based on the tenet of bilateral movement practice; however, the additional effect of bilateral robotic priming combined with these two therapies is unclear. Objectives: This study examined the effects of two hybrid therapies, robotic priming combined with MT and robotic priming combined with BULT, in stroke survivors. Methodology: The study randomized 31 participants to groups that received robotic priming combined with MT (n = 15) or robotic priming combined with BULT (n = 16). Outcome measures included the Fugl–Meyer Assessment (FMA), the revised Nottingham Sensory Assessment (rNSA), the Chedoke Arm and Hand Activity Inventory (CAHAI), and accelerometer data. Results: Both groups showed statistically significant within-group improvements in most outcome measures. Significant between-group differences and medium-to-large effect sizes were found in favor of the group that received robotic priming combined with MT based on the FMA distal part subscale scores, FMA total scores, and accelerometer data. Conclusion: Robotic priming combined with MT may have beneficial effects for patients in the improvements of overall and distal arm motor impairment as well as affected arm use in real life. Additional follow-up, a larger sample size, and consideration of the effect of lesion location or different levels of cognitive impairment are warranted to validate our findings in future studies. Clinical trial registration:www.ClinicalTrials.gov, identifier NCT03773653.